Frequency of median nerve tightness and its association with upper limb functions among smartphone users of a public sector university, Karachi - Latif, Amber; Ahmed Mirza Baig, Aftab; Abdul Wajid, Syed; Ali, Syed Shahzad (Journal of the Pakistan Medical Association, 2022)
Objective: To determine median nerve tightness in smartphone users, and to compare the upper limb functions between those with and without median nerve tightness. Method: The cross-sectional, observational study was conducted at the Institute of Physical Medicine and Rehabilitation, Dow University of Health Sciences, Karachi, from March 2020 to January 2021, and comprised subjects of either gender aged 20-40 years who had been using smartphone for >1 year. Body mass index was calculated. The participants were evaluated using upper extremity functional index-15. A hand-held dynamometer was used to assess handgrip strength, and a pinch meter assessed the pinch strength. Manual upper limb tension test 1 was used for median nerve tightness. Frequencies and percentages were drawn for all categorical variables. Data was analysed using SPSS 22. Results: Of the 277 subjects, 198(71.5%) were females. The largest group 176(63.5%) was aged 21-25 years. The mean upper limb functional index was 84.24±15.09. Also, 113(40.8%) subjects were positive for left-side median nerve tightness and 122(44%) were positive on the right side. There was no significant association between median nerve tightness and upper extremity function (p>0.05). The association, however, was significant with the duration of mobile usage in years (p<0.05). Conclusion: Prolonged overuse of smartphone may lead to symptoms of median nerve tightness, but it was not found to have an effect on upper limb function, handgrip and pinch strength. Key Words: Adults, Dynamometer, Hand strength, Middle-aged people, Mobile phone, Pinch strength, Upper extremity.